Severe H1N1-infection during pregnancy - Bowkalow, Sandy (Arch Gynecol Obstet, 2011)
H1N1 is known to induce fulminant courses in youths and young adults. We report the case of a 24-year gravida 4 para 2 with singleton pregnancy admitted to obstetrical unit for fever up to 38°C during the 20th week of a so far uncomplicated pregnancy. Ultrasound examination and urine test was inconspicuous. Throat complaints were initially relieved during antibiotic therapy, but the patient developed dyspnea with progressing signs of cyanosis. Intubation was necessary on the fifth day because of decreasing oxygen saturation. Coincidentally, progressive pancytopenia and increased inflammatory activity was recorded. Echocardiography, blood cultures, and bronchial lavage brought no pathological findings, but CT revealed acute respiratory distress syndrome and hepatomegaly. Recent human immunodeficiency virus, cytomegalic virus, herpes simplex virus, classical influenza and parainfluenza infections were excluded. An H1N1-infection was confirmed by PCR on the sixth day. The antiviral therapy was changed from zanamivir to oseltamivir. Extracorporeal membrane oxygenation was necessary due to insufficient oxygen saturation by mechanical ventilation. Until this time, pregnancy seemed to be unimpaired, but a sudden spontaneous expulsion of the fetus occurred on the seventh day (weight 460 g, no anomalies detectable). Curettage post abortem was not necessary. As a result of the antiviral therapy, H1N1-DNA was not detectable at day 16. Despite all endeavors, the respiratory situation could not be improved significantly; the patient additionally developed multiorgan failure during the time course and died on the 28th day of treatment. The recent case illustrates a very dangerous and imposing course of an H1N1-infection during pregnancy.